Enhanced hepatocyte survival and anti-apoptosis via Akt by Diallyl trisulfide, augments hepatic regeneration through hydrogen sulfide in partially hepatectomized rats - S. Nithyananthan; Shreyoshi Guha; Ishfaq Hassan Mir; C. Thirunavukkarasu (Elsevier, 2021)
Background: The hepatic resecting is the final decision for advanced end-stage liver diseases. Live donor liver transplantation is employed in the medical scenario due to less donor availability. It is mandatory to understand the signaling and therapeutic strategy to enhance hepatic regeneration to avoid small-for-size syndrome. Hence this current study was employed to explore the importance of H2S signaling in hepatic regeneration. Methods: The propargyl glycine (PAG) was used to inhibit H2S production, and garlic organosulfur, diallyl trisulfide (DATS), was an H2S donor in 70% partially hepatectomized male Wistar rats. The hepatectomized liver was allowed to regenerate for 48 h. The liver regeneration was scrutinized by analyzing the proliferative markers PCNA & Ki-67 and the apoptotic markers such as Bcl & Bcl-xL and hepatic antioxidants and serum liver markers. Results: The inhibition of H2S signaling displayed reduced hepatic regeneration rate and elevated liver index. The elevated serum liver marker enzymes such as AST, ALT & ALP further confirmed the hepatocyte damage. DATS administration to the regenerating liver demonstrated enhanced hepatic antioxidants (SOD, catalase, & GSH) and regenerative potential (PCNA & Ki-67). Histological findings supported the DATS enhanced liver regeneration. Western blot profiling of DATS supplied regenerating liver displayed increased expression of Bcl-xL and Akt phosphorylation with reduced Bad. Conclusion: This study concludes that the H2S signaling in the partial hepatectomized liver through DATS mediated Bcl-xL and Akt phosphorylation, enhancing hepatocyte survival and hepatic regeneration.